Analysis of the Pollution Index of Cadmium and Lead in Paddy Fields in Tempuran Subdistrict, Karawang Regency - Alfan Adhi Nugroho; Gina Lova Sari; Wilma Nurrul Adzillah (Jurnal Biologi Tropis, 2026)
Heavy metal contamination in agricultural soils has become an increasing environmental concern due to its potential impact on food safety and ecosystem sustainability. This study aims to analyze the concentration and contamination levels of heavy metals Cadmium (Cd) and Lead (Pb) in paddy fields located in Tempuran District, Karawang Regency. This region is one of the national rice production centers and is vulnerable to heavy metal accumulation due to intensive use of fertilizers and pesticides. The research was conducted in 14 villages, with disturbed soil samples collected for heavy metal and texture analysis, and undisturbed soil samples collected for porosity and permeability analysis. The main parameters analyzed were Cd and Pb concentrations using the ICP-OES method based on SNI 8910:2021. In addition, the pipette method was used for soil texture analysis; bulk and particle densities were used for porosity calculation; and the percolation method was used to measure permeability. Secondary data included the frequency of fertilizer and pesticide application, land use, age, and harvest periods. Results showed that Cd and Pb concentrations at all sampling locations remained below the threshold limits set by quality standards. Pollution assessment using the Contamination Factor (CF), Pollution Load Index (PLI), Geo-accumulation Index (Igeo), and Ecological Risk Index (Er) indicated that paddy fields in Tempuran District are categorized as uncontaminated to very low risk.